Level of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) Attack on Corn (Zea mays L.) Plants at Different Altitudes - Iyan Yuantara; Widyo Yuherdin; Lucky Firdaus Putra; Umi Trisnaningsih; Ismail Saleh (Jurnal Agrosci, 2025)
Background. One of the causes of low corn yields is the infestation of fall armyworms. Effective pest control techniques must consider the behavior of this pest. Therefore, it's essential to understand whether altitude influences the level of fallarmyworm infestation. Aims. This study aims to determine the relationship between altitude and the intensity of attacks and the intensity of damage caused by armyworms. Methods. The study was conducted at three different altitudes. Each altitude was represented by two villages, resulting in a total of six villages across two different regencies: Kuningan and Cirebon. The research method used was a survey with purposive sampling. Result. The study's results showed that altitude had a significant negative correlation with attack intensity, but not with damage intensity. Implementation. Fall armyworm control techniques will differ in different locations, depending on the altitude